Phase transformations induced by implantation of ¹²C⁻ ions into α-Fe and AISI 304 and 316 stainless steels studied by CEMS and SEM - Cabanillas, Edgardo Domingo (1994)
Samples of AISI 304 and 316 stainless steels, initially in austenitic (first set) and martensitic states (second set) and α-Fe (third set), were implanted with 180 keV¹²C⁻ to a dose of 10¹⁷ atoms/cm² at room temperature. Surfaces were examined by SEM (scanning electron microscopy) and the crystalline-phase fractions were estimated through CEMS (conversion electron Mossbauer spectroscopy). Different grades of etching were produced by sputtering during the implantations on the stainless steel samples depending on the previous crystallographic states. CEMS data reveal the γ → α′ transformation in the initially martensitic samples and no noticeable modifications as a result of the implantation on α-Fe and austenitic samples.